DETERMINAN HARGA SAHAM PADA PERUSAHAAN RETAIL YANG TERBIT DI BURSA EFEK INDONESIA - Sekar Waskitho Agung; Pangestu, Retno (Perwira Journal of Economics & Business, 2023)
The purpose of this study is to provide evidence regarding the influence of liquidity and profitability of companies on stock prices. The financial ratios studied are Current Ratio and Gross Profit Margin as independent variables and stock prices as the dependent variable. The number of samples used in this study are retail companies registered on the IDX that are actively traded from 2019 to 2021. The sampling method used is purposive sampling where sampling is carried out based on certain conditions. The statistical method used in this study is the multiple regression method. The results of this study indicate that the ratio variables Current Ratio and Gross Profit Margin statistically simultaneously do not have a significant effect on predicting stock prices to be traded. Meanwhile, statistically the partial variable Gross Profit Margin has a significant effect on predicting stock prices that will be traded on the stock exchange.